Knowledge and expectations on renewable energy among business, economics and accounting students in a Malaysian university - Jainurin Justine; Mohd Allif Anwar Abu Bakar; Mohd Rizwan Abd Majid; Rostika Petrus Boroh (FTMS College, 2019)
The United Nations Development Programme (UNDP) is promoting affordable and clean energy as one of the 17 Sustainable Development Goals (SDGs) for countries around the world to achieve by 2030. However, to date, the percentage of renewable energy being used Malaysia is still rather low. As existing university students are future leaders of the country, it is important to gauge their knowledge and expectations regarding renewable energy as related to the SDGs. This paper presents the results of a questionnaire survey carried out among 207 undergraduate business, economics and accounting students in a Malaysian public university. While the research results generally showed good knowledge and high expectations among the students on renewable energy, there were significant findings that can be used by relevant stakeholders to improve students’ knowledge and exposure to renewable energy and indirectly contribute to the acceptance of using these energy sources in Malaysia in the future. The paper concludes with suggestions for further research.